"From Arunachala": A Hindu-Christian Understanding of Holy Mountains - Chellappa, Gregory T. Basker (Interreligious studies and intercultural theology, 2017)
This paper discusses the commonalities/differences between the understandings of holy mountains in Hinduism and Christianity. The first part deals with Ramana Maharshi's understanding of the holy mountain Arunachala-his attraction to and reinterpretations of it. The second part presents Abhishiktananda's views on Arunachala, particularly with regard to Christian mysticism. Here the focus is on how he engaged in an interreligious interpretation of the mountain. In the final section, the paper explores the implications of such studies to the field of Comparative Religions. The paper deals with the following questions: Do comparative studies of religious concepts produce metanarratives for further investigation? Do similarities/dissimilarities point to a dependence/autonomy of concepts? Are there enduring patterns to look for in future in such intercultural hermeneutical exercises?